Metabolic effects of monounsaturated fatty acidâˆ’enriched diets on glycaemic control in patient with type 2 diabetes: an evidence-based case report - Krisadelfa Sutanto; Diana Sunardi; arieska felicia (World Nutrition Journal, 2023)
Introduction: Diabetes mellitus type 2 (T2D) is the most common type of diabetes. There is an ongoing debate as to whether nutrient quality or quantity is mainly responsible for the effects on hyperglycaemic control of patients with T2D. Monounsaturated fatty acid (MUFA) has a metabolic effect in reducing the risk factor for metabolic syndrome to prevent and control hyperglycaemia in patients with T2D and is recommended by professional organizations. Methods: Literature searching was conducted by advanced searching in Pubmed, Cochrane Library, Scopus, and ProQuest database using MeSH Terms combined with Title/Abstract. After removing duplicates, the literature were screened based on the eligibility criteria. Critical appraisal and level of evidence of the selected literature were determined based on Oxford Centre for Evidence-Based Medicine. Results: Two selected literature were relevant to answer our clinical question, both literature are systematic review/meta-analysis studies. The first literature is a study by Fumiaki et al. (2016), while the second is by Frank Qian et al. (2016). All literature provided evidence that a diet high in MUFA could improve glucose-insulin homeostasis among patients with T2D. These effects were marked by lower fasting blood glucose and haemoglobin A1c (HbA1c), and insulin level in the enriched MUFA diet group compared to PUFA. Conclusion: Nutrient quality is mainly responsible for the effects on glycaemic control profile in patients with T2D, with a high MUFA diet consistent with favourable effects to improve fasting glucose and HbA1c.